Prognostic Significance of Pre- to Postoperative Dynamics of Sarcopenia for Patients with Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy - Chen, Shuqiu; He, Ting; Sun, Si; Wu, Jianping; Xu, Bin; Mao, Weipu; Chen, Ming (Frontiers in Surgery, 2022)
Background: The aim of this study was to investigate the prognostic role of the dynamics of sarcopenia in the pre- to postoperative for patients with renal cell carcinoma (RCC) undergoing laparoscopic nephrectomy. Methods: This study included 261 patients who underwent laparoscopic nephrectomy between 2014 and 2019. The skeletal muscle index (SMI) of the L3 lumbar region was used to assess sarcopenia. The overall population was divided into four groups according to the dynamics of sarcopenia from pre- to postoperative: group 1 (both pre- and postoperative sarcopenia), group 2 (preoperative non-sarcopenia to postoperative sarcopenia), group 3 (preoperative sarcopenia to postoperative non-sarcopenia), and group 4 (both pre- and postoperative non-sarcopenia). The endpoints of the study were overall survival (OS) and cancer-specific survival (CSS). Results: Of the 261 patients who underwent laparoscopic nephrectomy, 103 (39.5%) had preoperative sarcopenia and 183 (70.1%) had postoperative sarcopenia. Patients with pre- or postoperative sarcopenia had poor survival outcomes. Sarcopenia dynamic was a better predictor of OS (AUC=0.737) and CSS (AUC=0.696) in patients with RCC than pre- and postoperative sarcopenia, and patients in group 4 of sarcopenia dynamic had the best OS and CSS. In addition, sarcopenia dynamics was an independent risk factor for OS and CSS, with a 94.5% reduction in OS risk (HR=0.055, 95% CI 0.007-0.407, p=0.003) and a 91.9% reduction in CSS risk (HR=0.081, 95% CI 0.011-0.616, p=0.015) in the group 4 compared with the group 1. Conclusion: Our study is the first to assess the prognostic value of pre- and postoperative sarcopenia dynamics in patients with RCC.